Surabaya Youth's Multicultural Attitude towards Global Citizenship (Phenomenological Study in High School Culture Junior) - Habibah, Siti Maizul; Sapriya, Sapriya; Sundawa, Dadang; Fitriasari, Susan (The Journal of Society and Media, 2024)
The multicultural attitude of Surabaya youth plays an essential role in realizing inclusive and sustainable global citizenship. In an era of increasingly connected globalization, Surabaya youth are faced with complex and interrelated challenges that require understanding, tolerance, and respect for cultural diversity. Factors such as education, personal experience, social environment, and the media have a crucial role in shaping the multicultural attitudes of Surabaya youth. The multicultural attitude of Surabaya youth contributes to realizing global citizenship through participation in cross-cultural activities, understanding global issues, and efforts to build harmonious relations between nations. Surabaya youth broaden their understanding of cultural diversity by engaging in cross-cultural activities and promoting positive intercultural dialogue. Understanding global issues enables them to play an active role in solving global challenges and fighting for sustainable solutions. Through harmonious international relations, the youth of Surabaya have a positive impact on building a more just, inclusive, and equitable world